New Meanings of the International Words of the Administrative Lithuanian Language - Vladarskienė, Rasuolė (Taikomoji kalbotyra, 2014)
The article refers to the data of The Database of New Borrowings, collected in the period of 1998–2010. An attempt is made to analyse the evolvement of new meanings of some international words and to identify the main tendencies. The Lithuanian administrative language is well maintained and innovations occur very seldom; however, if they occur, they tend to rapidly spread to other areas of standard language. After joining the European Union, with an influx of the EU documents translated into the Lithuanian language, the influence of the English language on the Lithuanian administrative language became unquestionable. This is particularly obvious in the international words used in administrative language. First of all, new meanings of international words conveying the original language meaning appear in the translated documents, afterwards the meanings can be found in Lithuanian documents and later may also be found in other language usage areas. The article discusses the new meanings of international adjectives and their suitability for administrative language. The paper also analyses some cases of polysemous nouns, which have preserved in their new international meanings an obvious link to the original meaning of the word. Some new meanings of international words find their place in standard Lithuanian; others are replaced by their Lithuanian equivalents or more traditional international words.